(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article analyses the effects of the linguistic engineering of modern Balkan languages in newly formed former Yugoslav states in the beginning of 1990’s. Each of the newly formed states conducted a deliberate policy of linguistic distancing. New language norms were developed on the basis of local historical and dialectic principles, in accordance with regional folk and literary dialects. In Croatia the language policy was followed by policy of purism, archaisms and localisms from Kajkavian and chakavian dialects were purposefully incorporated into literary norms. In Croatia there was a specific attitude towards borrowings from other languages, especially from Slavic and Oriental languages. Language corpus planners aimed to make Croatian extremely different from other languages in the region, especially from Serbian. If Croats tried to purify own language from oriental lexical idioms, Bosnians on the contrary actively incorporated such borrowings, especially from Oriental / Muslim languages. Bosnians aimed to make their language ideologically different from others in the region, making Islam the ideological core of new literary standard. In most cases the phonological structure of words has changed. In Montenegro the process of codification of the new literary standard was initiated later than in other states. New Montenegrin language standard has three new phonemes which are absent in other languages of the region. As in other states of the region, Montenegrin was codified on numerous local dialects, and therefore was not widely accepted by Montenegrins. The lexical and phonological structures of contemporary Balkan languages are of particular interest for ethno-linguistic anthropology and sociolinguistics since they reflect the socio-political transformations that have occurred in these states in the end of XXth century and the beginning of XXIst century.